Implementation of Subsidized Fertilizer Distribution Policy in South Minahasa Regency - Kordak, Devie; Pangkey, Itje; Pangkey, Itje; Kairupan, Sisca B. (Technium Social Sciences Journal, 2025)
This research aims to find out, analyze and describe the implementation of subsidized fertilizer distribution policies in the Ranoiapo district of South Minahasa regency and the determinant factors. This research uses qualitative method. The focus of this research is the mechanism of distribution of subsidized fertilizer policy in Ranoiapo District of South Minahasa Regency and the determinant factors of subsidized fertilizer distribution policy in Ranoiapo District of South Minahasa Regency with indicators: socialization, mechanism of subsidized fertilizer distribution, implementing apparatus, and ability to master technology. The results showed that 1) Socialization activities of subsidized fertilizer distribution in South Minahasa Regency, especially in Ranoiapo District, have not run optimally. It takes an active role of the government in this case agricultural extension workers as a companion to farmer groups in preparing the Definitive Plan of Group Needs (RDKK); 2) The mechanism of subsidized fertilizer distribution in South Minahasa Regency, especially in Ranoiapo district, is not implemented in accordance with the decision of the Director General of Agricultural Infrastructure and Facilities Number 34.11/KPTS/RC.210/B/12/2023 concerning Technical Guidelines for the Management of Subsidized Fertilizers for Fiscal Year 2023; 3) The local government as the implementing apparatus and policy maker in the distribution of subsidized fertilizers does not play an active role in carrying out its duties and functions. Implementation of monitoring and evaluation from the government as one of the factors that must be done to answer the various obstacles faced in the field; 4) Farmers as subsidized fertilizer users do not fully understand and understand the use of technology, in this case the Farmer Card which is one of the products of the government program to record and compile farmers' needs for fertilizers and as a means of redeeming subsidized fertilizers at kiosks or official retailers.